3D SURFACE AND SUBSURFACE MODELING FOR NORTH JAKARTA COASTAL ROB FLOODING - Zukhrufiati Asyifa, Mutiara
Coastal flooding is a natural disaster that can endanger people and property and cause environmental and economic losses. North Jakarta, as one of the administrative cities in the capital city, is experiencing population growth that triggers the rapid development of various facilities and economic growth. This growth increases the demand for groundwater that risks over pumpage, causing land subsidence and tidal flooding. This study aims to build a three-dimensional surface and subsurface model of the North Jakarta coastal area and estimate economic losses due to coastal flooding. LiDAR data in 2010 and 2022 were used to build a three-dimensional surface model and coastal flood modeling. Subsurface modeling was conducted through interpolation of kriging method from the results of layer drilling in the North Jakarta area in 2010. The damagescanner model is used to assess the economic loss as a function of hazard, exposure, and vulnerability. The modeling results show that the subsoil in the coastal area of North Jakarta is dominated by sand and sandy clay types. In 2023, North Jakarta is projected to be inundated by coastal floods with a maximum depth of 3.52 meters (with dike) and 5.2 meters (without dike). The estimated total value of losses due to coastal flooding in Marunda, Muara Angke, Muara Baru, and JIS reaches 6.8 trillion Rupiah for the dike scenario, while the worst-case scenario calculation without dike can reach 18.6 trillion Rupiah.